Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Given f(x)=x^2+2x+1
Find f(x+h-f(x)


Sagot :

f(x) = x² + 2x + 1
f(x + h - f(x))
f((x² + 2x + 1) + (1 + 2 + 1) - f(x² + 2x + 1)))
f((x² + 2x + (1 + 1 + 2 + 1) - f(x² + 2x + 1)))
f((x² + 2x + 5) - f(x² + 2x + 1))
f(x² - x² + 2x - 2x + 5 - 1)
f(4)
f(4) = 4² + 2(4) + 1
f(4) = 16 + 8 + 1
f(4) = 25